2014
DOI: 10.1021/ic502547y
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Proton Reduction by Dimeric Nickel Complex of a Sterically Demanding Pincer-type NS2 Aminobis(thiophenolate) Ligand

Abstract: Basic methanolysis of a sterically hindered aminobis(S-arylthiocarbamate) affords a novel aminobis(thiophenolate) pincer-type ligand NS22–; the in situ generated dianion reacts cleanly with Ni2+ and Zn2+ resulting in dimeric complexes with bridging thiophenolate ligands, as determined spectroscopically and by X-ray crystallography. The C2-symmetric [Ni(NS2)]2 dimer (1) has a square planar coordination geometry around the Ni2+ ions, while the [Zn(NS2)]2 analogue (2) is characterized by a distorted tetrahedral g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…Those planes around the nickel centers in 1 , defined by N1, S1, S2, and S4 (N1, S1, S2, and S1 bridge for 2 ), are joined along one edge by means of S1 and S2 (S1 and S1 bridge for 2 , see Table and Figure ); therefore, for both complexes, each monomeric unit has a terminal thiophenolate ligand that may be considered electron‐rich (S4 and S3 atoms for 1 and S2 for 2 in Figure ) . Additionally, the two coordination planes around the nickel centers in 1 define a dihedral angle ( θ ) of 81.3(5)° (hinge angle), leading to a Ni⋅⋅⋅Ni distance of 2.7295(8) Å, which is comparable to that previously reported for [Ni 2 ( κ ‐ N,S,S,S′ ‐N iBu {CH 2 (MeC 6 H 2 R′)S} 2 ) 2 ] ( 4 ; R′=3,5‐(CF 3 ) 2 C 6 H 3 , with a Ni⋅⋅⋅Ni distance of 2.702(8) Å and θ =85.5(4)°) . On the other hand, in 2 , the hinge angle is θ =180(2)° (Table and Figure ), resulting in a coplanar arrangement with a considerably longer Ni⋅⋅⋅Ni distance of 3.364(4) Å.…”
Section: Resultssupporting
confidence: 81%
“…Those planes around the nickel centers in 1 , defined by N1, S1, S2, and S4 (N1, S1, S2, and S1 bridge for 2 ), are joined along one edge by means of S1 and S2 (S1 and S1 bridge for 2 , see Table and Figure ); therefore, for both complexes, each monomeric unit has a terminal thiophenolate ligand that may be considered electron‐rich (S4 and S3 atoms for 1 and S2 for 2 in Figure ) . Additionally, the two coordination planes around the nickel centers in 1 define a dihedral angle ( θ ) of 81.3(5)° (hinge angle), leading to a Ni⋅⋅⋅Ni distance of 2.7295(8) Å, which is comparable to that previously reported for [Ni 2 ( κ ‐ N,S,S,S′ ‐N iBu {CH 2 (MeC 6 H 2 R′)S} 2 ) 2 ] ( 4 ; R′=3,5‐(CF 3 ) 2 C 6 H 3 , with a Ni⋅⋅⋅Ni distance of 2.702(8) Å and θ =85.5(4)°) . On the other hand, in 2 , the hinge angle is θ =180(2)° (Table and Figure ), resulting in a coplanar arrangement with a considerably longer Ni⋅⋅⋅Ni distance of 3.364(4) Å.…”
Section: Resultssupporting
confidence: 81%
“…Castillo reported on an N , N ‐bis(2‐thiophenol)methylisopropylamine that binds Ni II in the form of a dimeric thiolate‐bridged complex. Electrochemical reduction (oxidation) of the di‐Ni II precursor in THF has been suggested to afford di‐Ni I (di‐Ni III ) species that initiate electrocatalytic proton reduction (evolution) from HBF 4 (borohydride), as shown in Scheme . Although neither of the Ni species has been substantially characterized, these findings add to the general notion that low‐ and high‐valent binuclear complexes of Ni play a role in a variety of reactions…”
Section: Introductionmentioning
confidence: 99%
“… Electrochemical generation of putative di‐Ni I or di‐Ni III species from a (μ‐S) 2 Ni II 2 complex for electrocatalytic reduction and evolution of protons …”
Section: Introductionmentioning
confidence: 99%
“…One can differentiate between structural motifs in which electronic coupling of the Ni(I) ions either occurs through bonding to (i) bridging conjugated π-systems in both syn-and antarafacial fashion, [1][2][3][4][5][6][7][8] (ii) bridging amido, 9 phosphido, 10 thiolato, 11,12 sulfido, 13 halogenido, [14][15][16][17] and hydrido 18 ligands in the form of Ni 2 (μ-X) 2 cores, (iii) bridging diphosphine, 19,20 and biphenyldiyl 15,21,22 ligands, or in the form of unsupported Ni-Ni bonds. One can differentiate between structural motifs in which electronic coupling of the Ni(I) ions either occurs through bonding to (i) bridging conjugated π-systems in both syn-and antarafacial fashion, [1][2][3][4][5][6][7][8] (ii) bridging amido, 9 phosphido, 10 thiolato, 11,12 sulfido, 13 halogenido, [14][15][16][17] and hydrido 18 ligands in the form of Ni 2 (μ-X) 2 cores, (iii) bridging diphosphine, 19,…”
Section: Introductionmentioning
confidence: 99%
“…2,5,9 The reversible formation of reactive Ni(I) species appears to represent one of the two major modes of reactivity displayed by binuclear Ni(I) complexes. [10][11][12] In the context of a reactivity study of thiolate complexes of Ni(I), Tatsumi and co-workers reported the structure of a binuclear Ni(I) complex with bridging arene and thiolate groups, see II in Scheme 1. 26 Despite the exact mechanism of this process remaining unresolved, dinickel(I) complexes have been reported to catalyse reductive C-C bond formation in a cooperative fashion, 15,21,22 to act as precursors in bimetallic catalytic group transfer reactions to form carbodiimides and isocyanates, 17,27 and to activate secondary silanes for the catalytic hydrosilation of unsaturated substrates.…”
Section: Introductionmentioning
confidence: 99%